2023
DOI: 10.3390/ph16010084
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation of Vaccinium ashei Leaf Extract in Eudragit® RS100-Based Nanoparticles Increases Its In Vitro Antioxidant and In Vivo Antidepressant-like Actions

Abstract: Depression is a major psychiatric disorder in Brazil and worldwide. Vaccinium ashei (V. ashei) leaves are cultivation by-products with high bioactive compound levels. Here, a hydroalcoholic extract of V. ashei leaves (HEV) was associated with Eudragit® RS100-based nanoparticles (NPHEV) to evaluate the in vitro antioxidant and in vivo antidepressant-like effects. Interfacial deposition of the preformed polymer method was used for NPHEV production. The formulations were evaluated regarding physicochemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Blueberry leaves, which have been used mainly for medicinal purposes, are considered essentially as waste or by-products. Various health benefits were reported for leaf extracts from the Vaccinium species [29][30][31][32]. A large number of studies have shown that exogenous ABA stimulates anthocyanin accumulation of blueberry fruits [7,43,44].…”
Section: Exogenous Aba Promoter Anthocyanin Accumulation Of Blueberry...mentioning
confidence: 99%
See 1 more Smart Citation
“…Blueberry leaves, which have been used mainly for medicinal purposes, are considered essentially as waste or by-products. Various health benefits were reported for leaf extracts from the Vaccinium species [29][30][31][32]. A large number of studies have shown that exogenous ABA stimulates anthocyanin accumulation of blueberry fruits [7,43,44].…”
Section: Exogenous Aba Promoter Anthocyanin Accumulation Of Blueberry...mentioning
confidence: 99%
“…Blueberry (Vaccinium corymbosum) is a popular fruit worldwide, in part due to the health benefits associated with its rich flavonoid compounds, particularly anthocyanins [27,28]. The fruits of the Vaccinium species are the main commercial products, whereas the leaves have been used mainly for medicinal purposes [29][30][31][32]. In the wild lowbush blueberry (V. angustifolium) and lingonberry (V. vitis-idaea), the total antioxidant capacities in terms of radical scavenging activity and reducing power were much higher in the leaves of both plants as compared to their fruits, which were in correlation with phenolic contents including total flavonoids, anthocyanins, and tannins [33].…”
Section: Introductionmentioning
confidence: 99%